Special Education Teachers’ Perceptions of Parental Involvement in Inclusive Education - Mizyed Hyassat; Asem Al-Bakar; Ahmad Al-Makahleh; Nawaf al-Zyoud (Education Sciences, 2024)
(1) Background: It is widely agreed that mutual partnerships between school staff and parents of students are key to creating robust frameworks of inclusive education for students with disabilities. This study explores special education teachers’ perceptions of involving parents of students with disabilities in mainstream schools in Jordan. (2) Methods: This research employs a descriptive quantitative method in the form of a Google-Forms-based online questionnaire with closed-ended questions. (3) Results: The findings indicate that parents were moderately involved in the education of their disabled children; that these parents perceived teachers and school principal to be instrumental in encouraging their involvement in this respect; and that parents face many obstacles to such involvement in their children’s education. (4) Conclusions: The findings point to a need for policymakers to create legislation that enables and mandates the involvement of parents with children with disabilities in inclusive education settings in order to implement constructive models of parental involvement where parents can be treated as equal partners in the educational process.